Advanced Surgical Trauma Care Course – Evaluation of a Fracture Simulation Course Concept with Intact Soft Tissue - Wegmann, Kilian; Rausch, Valentin; Burkhart, Klaus Josef; Hackl, Michael; Leschinger, Tim; Müller, Lars (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Purpose Currently, surgical training in the clinical scenario is limited by duty-hour restrictions as well as an increasing specialization within the numerous surgical fields. In such an environment, surgical training in subspecialties becomes both, more important and challenging. Against this background, purpose of the present study was to evaluate a new course format for advanced training in fracture treatment. In the studied course format, cadaveric wrist or elbow specimens with prefabricated fractures were used with the aim of improving the learning effect for the attendees. On these specimens, operative treatment with specific osteosynthetic implants was performed under radiographic control. We hypothesized that simulation in a complex scenario such as the one used in the studied course format leads to a subjectively better learning effect regardless of prior surgical experience.Methods 205 participants in 16 courses between 2016 and 2018 were surveyed regarding their operative experience, previously attendances of trauma care trainings and subjective learning effect in the surveyed course and the trainings attended previously. Based on a ten-step scale, results in the subjective learning effect were compared between the investigated course and other trainings and to the individual operative experience.Results The learning effect of the surveyed fracture courses was assessed with a median of 9/10 for the theoretical part and 10/10 for the practical part, significantly better than in trainings attended previously. The surveyed participants reported that they each performed 308 operations per year on average. Other course formats were attended significantly more frequent than courses on prefractured human specimens. The respondents reported a subjectively higher learning effect of the evaluated course concept in comparison to previously attended courses in practical and theoretical aspects.Conclusions The reported innovative course format is an efficient concept for education in surgical trauma care, suited for more novice and advanced surgeons.
Keywords: simulation; education; surgical education; course; elbow